Using Milk Urea Nitrogen to Evaluate Diet Formulation and Environmental Impact on Dairy Farms - J.S. Jonker; R.A. Kohn (The Scientific World Journal)
Reducing nitrogen (N) excretion by dairy cattle is the most effective means to reduce N losses (runoff, volatilization, and leaching) from dairy farms. The objectives of this review are to examine the use of milk urea nitrogen (MUN) to measure N excretion and utilization efficiency in lactating dairy cows and to examine impacts of overfeeding N to dairy cows in the Chesapeake Bay drainage basin. A mathematical model was developed and evaluated with an independent literature data set to integrate MUN and milk composition to predict urinary and fecal excretion, intake, and utilization efficiency for N in lactating dairy cows. This model was subsequently used to develop target MUN concentrations for lactating dairy cattle fed according to National Research Council (NRC) recommendations. Target values calculated in this manner were 8 to 14 mg/dl for a typical lactation and were most sensitive to change in milk production and crude protein intake. Routine use of MUN to monitor dairy cattle diets was introduced to dairy farms (n = 1156) in the Chesapeake Bay watershed. Participating farmers (n = 454) were provided with the results of their MUN analyses and interpretive information monthly for a period of 6 months. The average MUN across all farms in the study increased in the spring, but the increase was 0.52 mg/dl lower for farmers receiving MUN results compared to those who did not participate in the program. This change indicated that participating farmers reduced N feeding compared to nonparticipants. Average efficiency of feed N utilization (N in milk / N in feed x 100) was 24.5% (SD = 4.5). On average, farmers fed 6.6% more N than recommended by the NRC, resulting in a 16% increase in urinary N and a 2.7% increase in fecal N compared to feeding to requirement. N loading to the Chesapeake Bay from overfeeding protein to lactating dairy cattle was estimated to be 7.6 million kg/year. MUN is a useful tool to measure diet adequacy and environmental impact from dairy farms.